Political Economic Transactions in Political Contest: Relationship Between Poverty and Money Politics in Indonesia - Ratnia Solihah; Triono Triono (Research Collaboration Community (RCC), 2022)
In political contestation, the issue of poverty is still considered effective because it can be felt directly by the community. The contestants' use of poverty data for certain political purposes will make the sympathy of many people and prove to be able to gain people's votes because they feel represented. In the process, the contestants, both incumbent and opposition, will look for loopholes in each of their campaign programs regarding poverty suppression. On the other hand, our political contestation event is also still being polluted by the practice of money politics. The wide gap in economic inequality will trigger the practice of money politics. This practice is increasingly widespread by the presence of the rich elite as material givers and voters who are below the poverty line as recipients. Those who receive money sometimes do not really think about the consequences that will be received, such as bribery and vote buying which are clearly against the law, because the most important thing for them is to get money and be able to fulfill their needs. In this case, money politics is also growing and there are many kinds, not only in the form of money but those who carry out this practice will bandage it so that it is not too visible, such as by providing assistance, rewards, and material or other valuable things as well as by promising something. later inserted when campaigning by candidates or campaign teams in political contestations. To discuss these problems, the author uses a qualitative method through a literature study, namely collecting and analyzing data using various relevant references on poverty and money politics. This paper will explain about the existence of political-economic transactions in political contestation, the causal factors, the relationship between poverty and money politics, as well as efforts to prevent money politics in political contestation, which are explained through a poverty perspective.